2017
DOI: 10.1016/j.chemosphere.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Potential phosphorus eutrophication mitigation strategy: Biochar carbon composition, thermal stability and pH influence phosphorus sorption

Abstract: Phosphorus (P) eutrophication is a major pollution problem globally, with unprecedented amount of P emanating from agricultural sources. But little is known about the optimization of soil-biochar P sorption capacity. The study objective was to determine how biochar feedstocks and pyrolysis conditions influences carbon (C) thermal stability, C composition and pH and in turn influence the phosphorus sorption optimization. Biochar was produced from switchgrass, kudzu and Chinese tallow at 200, 300, 400, 500, 550,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 51 publications
3
53
2
1
Order By: Relevance
“…(), that biochar induced ethylene emission was significantly decreased after 20 days in moist soil. A previous study found positive correlation between pyrolysis temperature and P sorption capacity of biochar ( Ngatia et al., ), indicating the greater P sorption capacity of high temperature biochar. The main mechanism of P sorption to biochar has been proposed to be the precipitation of phosphate with calcium and magnesium ( Karunanithi et al., ), and sorption to the large surface area of biochar ( Trazzi et al., ).…”
Section: Discussionmentioning
confidence: 84%
“…(), that biochar induced ethylene emission was significantly decreased after 20 days in moist soil. A previous study found positive correlation between pyrolysis temperature and P sorption capacity of biochar ( Ngatia et al., ), indicating the greater P sorption capacity of high temperature biochar. The main mechanism of P sorption to biochar has been proposed to be the precipitation of phosphate with calcium and magnesium ( Karunanithi et al., ), and sorption to the large surface area of biochar ( Trazzi et al., ).…”
Section: Discussionmentioning
confidence: 84%
“…3,4 Therefore, methods for reducing the concentration of phosphorus in contaminated water have become a hot topic in environmental science. 5 There are many ways of reducing the concentration of phosphorus in water, such as the membrane separation method, chemical precipitation method, biological degradation method, and so on, but each of these methods is highly targeted due to its specic application scope, 6,7 and so it is extremely important to nd a simple, low-cost method which could have a wide range of applications. Chemical adsorption could become one of the most promising phosphorus-containing waste-water treatment methods in the future because of its unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…Soil P exists in a range of organic and inorganic compounds that differ remarkably in their biological availability in the soil environment [14]. The inorganic P compounds preferentially couple with crystalline and amorphous forms of Al, Fe, and Ca [15] the coupling is highly influenced by soil pH [16]. Organic P in most soils is dominated by a mixture of phosphate diesters (mainly nucleic acids and phospholipids) and phosphate monoesters (example; mononucleotides, inositol phosphates) with smaller amounts of phosphonates (compounds with a direct carbon-phosphorus bond) and organic polyphosphates (for example; adenosine triphosphate) [17].…”
Section: Forms Of Nitrogen and Phosphorusmentioning
confidence: 99%